Nutrition, lifestyle factors, and blood pressure - Lin, Pao-Hwa.; Svetkey, Laura P. (Boca Raton : CRC Press, 2012)
'Aiming to increase awareness, this book covers measures to prevent health conditions and diseases that are associated with high blood pressure. The first section provides a comprehensive review of diet, nutrition, lifestyle, and blood pressure control. It also discusses the consequences of high blood pressure, including heart disease, kidney disease, diabetes, and stroke. The second section focuses on implementation of strategies to promote behavioral changes for blood pressure control. The final section addresses key subgroup populations and situations that require special considerations. Case studies demonstrate how lifestyle factors can be changed to control blood pressure'--
Includes bibliographical references and index.
Keywords: Hypertension -- Diet therapy; Exercise therapy; Self-care, Health